AC motor speed performance improvement using fuzzy logic control - Sidik, Mohd Azkar (2015)
This project focuses on the fuzzy logic controller design to control single phase induction motor. The controller strategy is done through phase angle control method. The phase angle is controlled by controlling the firing angle delay of the triac. This controller system is implemented and simulated using MATLAB Simulink software. The performance of the single phase induction motor are investigated and compared with the PID controller. Based on the simulation, fuzzy logic controller is suitable to control single phase induction motor because it can reduce the rise time, settling time, peak time and overshoot to 0.10s, 0.17s, 0.29s and 0.09 % OS respectively. The comparison between fuzzy logic controller and PID controller shows that the fuzzy logic controller gives better performance response with the rise time (Tr), the settling time (Ts), peak time (Tp) and overshoot (% OS) are 0.08s, 0.08s, 0.05s and 0.004% smaller than PID controller.